If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10(x + 2) = sqrt(13) + -7x Reorder the terms: 3x + -10(2 + x) = sqrt(13) + -7x 3x + (2 * -10 + x * -10) = sqrt(13) + -7x 3x + (-20 + -10x) = sqrt(13) + -7x Reorder the terms: -20 + 3x + -10x = sqrt(13) + -7x Combine like terms: 3x + -10x = -7x -20 + -7x = sqrt(13) + -7x Reorder the terms for easier multiplication: -20 + -7x = 13qrst + -7x Add '7x' to each side of the equation. -20 + -7x + 7x = 13qrst + -7x + 7x Combine like terms: -7x + 7x = 0 -20 + 0 = 13qrst + -7x + 7x -20 = 13qrst + -7x + 7x Combine like terms: -7x + 7x = 0 -20 = 13qrst + 0 -20 = 13qrst Solving -20 = 13qrst Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-13qrst' to each side of the equation. -20 + -13qrst = 13qrst + -13qrst Combine like terms: 13qrst + -13qrst = 0 -20 + -13qrst = 0 Add '20' to each side of the equation. -20 + 20 + -13qrst = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -13qrst = 0 + 20 -13qrst = 0 + 20 Combine like terms: 0 + 20 = 20 -13qrst = 20 Divide each side by '-13rst'. q = -1.538461538r-1s-1t-1 Simplifying q = -1.538461538r-1s-1t-1
| -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 | | log(6x+8)=log(12) | | -7(8k-8)=-392 | | 720/6 | | 3cos^2x=2 | | 6tons=Pounds | | 720/3 | | Y=-1/2(x-6)(x8) | | 2(3x+2)=4(2x-5) | | 8s-26+5s-15=180 | | 6b+4b=-12+8b | | 25*7+11*3+2*3= | | 2x^2+-8x-384=0 | | 2(x+2)=-2(x+6) | | 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= | | W-12=2w-36 | | 1/3✖️3/4 | | 1/3✖️3/4=3/8 | | 29*7+16*3+8*3= | | 6y-14=9y-5 | | -3(y+2)=7y-8+4(2y+4) | | .027+2-.035x=0 | | 540*10+160*3= |